Abnormal trunk control determines postural abnormalities in Amyotrophic Lateral Sclerosis - Krieg, Iris (NeuroRehabilitation, 2019)
BACKGROUND: Postural instability in Amyotrophic Lateral Sclerosis (ALS) occurs at an early stage of the disease and often results in falls. As ALS is considered a multisystem neurodegenerative disorder, postural instability may result from motor, sensory and central processing deficits. OBJECTIVE AND METHODS: We analysed postural control of 12 ALS patients and 12 healthy age-matched control subjects. Postural control was characterised by spontaneous sway measures and measures of postural reactions to pseudorandom anterior-posterior platform tilts, which were then correlated with clinical test scores. RESULTS: Spontaneous sway amplitudes and velocities were significantly larger and sway frequencies higher in ALS patients than in control subjects. ALS patients’ body excursions following platform tilts were smaller, with relatively higher upper body excursions. We found high correlations between abnormal postural reactions and clinical tests representing motor or balance deficits. CONCLUSIONS: We conclude that ALS patients’ postural abnormalities are mainly determined by an abnormal axial control and abnormally small body excursions as a function of support surface tilts, seemingly indicating better postural stabilization than control subjects. The latter contradicts the hypothesis that muscle weakness is the main source for this deficit. Instead, we suggest an altered central control strategy.